Surpassing the Target: How a Recruitment Campaign Transformed the Participant Accrual Trajectory in the Epilepsy Phenome/Genome Project. Issue 5 (14th July 2015) - McGovern, Kathleen; Karn, Catharine Freyer; Fox, Kristen; ,
Abstract: Participant recruitment challenges pervade the majority of publicly funded clinical trials. However, little is known about methods for enhancing participant accrual. The Epilepsy Phenome/Genome Project (EPGP), a multicenter study funded by the National Institute of Neurological Disorders and Stroke (NINDS), aimed to enroll a total of 5, 250 participants to better understand the genetic causes and phenotypic manifestations of epilepsy. However, similar to other trials, EPGP encountered recruitment challenges, and by the end of its first year, net enrollment was only 48% of the target for that time. To address this, EPGP established a National Participant Recruitment Campaign and began implementing and tracking the enrollment outcomes of a variety of proven and relatively novel recruitment methods. At the conclusion of the project, EPGP had successfully enrolled a total of 5, 445 participants, thus surpassing its enrollment target. Data pertaining to EPGP's National Participant Recruitment Campaign was analyzed retrospectively, and the results are reported here, so that other multicenter trials may consider these methods in their recruitment planning and potentially avoid the costly repercussions of participant accrual issues.